Мorphobiochemical indicators of blood as a tool for evaluating the efficiency of animal protein in goose nutrition - Nugmanova, A. E.; Baktygerey, N. K.; Нугманова, А. Е.; Бактыгерей, Н. К. (Жәңгір хан атындағы БҚАТУ, 2025)
The article presents the results of a study of the effect of animal protein in the diet on the morphobiochemical parameters of geese blood. The purpose of this study is to study the morpho-biochemical parameters of geese blood as indicators of the body's physiological response to the inclusion of animal protein in the diet. In the experiment, fish meal was used as an additional protein source for the experimental group, while the control group received a standard diet without animal protein. A comparative analysis of the control and experimental groups was carried out, significant changes in the levels of the main hematological (hemoglobin, erythrocytes, leukocytes) and biochemical (total protein, albumins, globulins) parameters were revealed. The results showed that the introduction of animal protein improves metabolic processes, as evidenced by significant changes in blood parameters. It has been established that morpho-biochemical parameters can be used as reliable indicators of adaptation and the general physiological state of a bird when changing its feeding strategy. The data obtained are of practical importance in the development of diets to increase productivity and resistance of geese to external factors. Additionally, it was found that the use of fishmeal has a positive effect on protein metabolism and potentially improves body weight gains. The results can be applied in the industrial poultry farming system to optimize the feeding of waterfowl.
Nugmanova, A. E. Мorphobiochemical indicators of blood as a tool for evaluating the efficiency of animal protein in goose nutrition / A. E. Nugmanova, N. K. Baktygerey, А. Е. Нугманова, Н. К. Бактыгерей. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2025. - № 1-1 (78). Ч. І. - Р. 329-339 (Uralsk). - ISSN 2305-9397
Keywords: научный журнал; журнал кокснво; ветеринария; птицеводство; geese; feeding; animal protein; morpho-biochemical parameters; биохимический состав